PELATIHAN PEMANFAATAN ARTIFICIAL INTELLIGENCE TOOLS UNTUK PENGEMBANGAN KONTEN EDUKASI KESEHATAN BAGI PETUGAS PUSKESMAS SUNGAI BULIAN - Ichsandi; Mulia Aminurrahman; Nadya Pingkan (AbdiMasya | Hira Institute, 2025)
This community service aims to improve the competence of Sungai Bulian Health Center officers in utilizing artificial intelligence (AI) tools to develop interesting and effective health education content through direct practice on smartphones. The background of the problem includes the limited digital skills of health center officers in rural areas, which hinders the delivery of preventive health information to the community. The activity was carried out through a two-day workshop training in December 2025, involving 25 health center officers as the main participants, with the main practice media in the form of personal smartphones or health centers. Training materials include an introduction to mobile-friendly AI tools such as the ChatGPT app for educational text generation, the Canva app with Magic Studio for visual design, and apps such as Microsoft Designer or Lensa AI for image generation, accompanied by hands-on smartphone-based practice and small group mentoring sessions. The results of the training showed an increase in participants' knowledge by 85% based on the pre-post test, with 90% of participants able to produce self-educational content directly from their smartphones. As a result, health center officers are now more efficient in disseminating health materials such as stunting and diabetes prevention through WhatsApp, Instagram, or TikTok. The conclusion of this activity emphasizes that smartphone-based AI training can strengthen the role of health centers as primary health education centers in remote areas